Analisis Hasil Gambar Ilustrasi Berdasarkan Aspek Proporsi, Perspektif dan Pencahayaan - Rizky Apriliani; Zulkifli Zulkifli (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to determine the students' ability to draw illustrations in applying the work of drawing illustrations in class VIII SMP Muhammadiyah 7 Medan based on proportions, perspectives and lighting. With the theme of the atmosphere of activities commemorating Indonesia's independence day. The population in this study were all students' works of class VIII SMP Muhamadiyah 7 Medan, namely all students' works and the sample was 21 students' works of class VIII-1 using the purposive sampling technique. This study uses a descriptive qualitative method to find out how the work of illustration images by class VIII students of SMP Muhammadiyah 7 Medan is viewed from the perspective of proportion, perspective and lighting. The findings of this study indicate that the overall ability of class VIII-1 students in drawing illustrations based on proportion, perspective and lighting has a good category with an average value (r) = 85.